Cytotoxic Effects of Alternariol, Alternariol Monomethyl-Ether, and Tenuazonic Acid and Their Relevant Combined Mixtures on Human Enterocytes and Hepatocytes - den Hollander, Danica; Holvoet, Celestien; Demeyere, Kristel; De Zutter, Noémie; Audenaert, Kris; Meyer, Evelyne; Croubels, Siska (Frontiers in Microbiology, 2022)
Alternariol (AOH), alternariol-monomethyl ether (AME) and tenuazonic acid (TeA) are major mycotoxins produced by fungi of the genus Alternaria and are common contaminants of food products such as fruits, vegetables, cereals and grains. Alternaria mycotoxins are known to cause relevant economic losses and to have a negative impact on human and animal health. EFSA stated in its scientific opinion that data on the toxicity of Alternaria mycotoxins in humans and livestock are generally lacking, precluding proper hazard characterization. This study aimed to fill some knowledge gaps by studying the in vitro cytotoxicity towards human intestinal epithelial cells (Caco-2) and hepatocytes (HepG2). Cytotoxic properties were assessed by flow cytometric analyses of remaining viable cells (i.e. propidium iodide negative) after mycotoxin exposure for 24-48 hours (h) versus solvent control. Treatment of cells with single doses of AOH, AME and TeA resulted in a dose-dependent loss of cell viability for both cell lines. Half maximal effective concentrations (EC50) of the different mycotoxins were comparable for the two cell lines. On HepG2 cells, EC50 values varying between 8 – 16 µg/mL, 4 – 5 µg/mL and 40 – 95 µg/mL were calculated for AOH, AME and TeA, respectively. On Caco-2 cells, EC50 values of 19 µg/mL and varying between 6 – 23 µg/mL and 60 – 90 µg/mL were calculated for AOH, AME and TeA, respectively. A general relative cytotoxicity ranking of about 1 = 1 >>> 3 was obtained for AOH, AME and TeA, respectively. Treatment of both cell lines with combined binary and ternary mixtures of AOH, AME and TeA in a 1:1:3 ratio, also showed a dose-dependent decrease of cell viability. For both cell lines, the binary combination of especially AME and TeA (1:3 ratio) but also of AOH and AME (1:1 ratio) significantly increased the cytotoxicity compared to the single compound toxicity, although mainly at the highest concentrations tested. The ternary combinations of AOH, AME and TeA induced only a slight increase of cytotoxicity compared to the single mycotoxins, again at the highest concentrations tested.